2013
DOI: 10.1007/s00404-013-2995-5
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid in the treatment of intrahepatic cholestasis of pregnancy: a randomized controlled trial

Abstract: UDCA improves maternal itching scores and liver function tests without interfering with the fetoplacental estrogen production in patients with ICP. UDCA is well tolerated by pregnant women. No fetal or neonatal side-effects could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Opioids, serotonin, and female sex hormones have all been implicated in the etiology of pruritus. Increased levels of endogenous opioids are reported in chronic liver disease [ 18 , 19 ] and treatment with an opioid antagonist is shown to reduce pruritus [ 20 22 ]. Serotonin is believed to induce pruritus by altering itch perception [ 17 ] and so serotonin reuptake inhibitors such as sertraline have reported to be effective in managing pruritus [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Opioids, serotonin, and female sex hormones have all been implicated in the etiology of pruritus. Increased levels of endogenous opioids are reported in chronic liver disease [ 18 , 19 ] and treatment with an opioid antagonist is shown to reduce pruritus [ 20 22 ]. Serotonin is believed to induce pruritus by altering itch perception [ 17 ] and so serotonin reuptake inhibitors such as sertraline have reported to be effective in managing pruritus [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 Rodrigo Z and Joutsiniemi T have also shown statistically significant improvement in maternal pruritus after UDCA treatment as compared to placebo. 16,17 Study by Glantz A showed more itch improvement in the placebo group compared to UDCA. 20 This may be because of a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done so far, comparing UDCA with other drugs or placebos, have shown variable results, especially concerning the perinatal outcome. [15][16][17][18][19][20][21][22][23] Due to these debates in the management of patients having obstetric cholestasis we planned this study. We compared the UDCA with placebo and observed the effects on maternal symptoms of pruritus, biochemical marker i.e.…”
Section: Introductionmentioning
confidence: 99%
“…UDCA appears to be the most efficient pharmacologic treatment. It has been shown that UDCA ameliorates pruritus and restores elevated liver function during ICP (Joutsiniemi et al, 2015;Joutsiniemi, Timonen, Leino, Palo, & Ekblad, 2014;Kondrackiene, Beuers, & Kupcinskas, 2005), without interfering with fetoplacental estrogen production (Joutsiniemi et al, 2014). It was more effective than cholestyramine and dexamethasone at reducing bile acid concentration (Kondrackiene et al, 2005).…”
Section: Introductionmentioning
confidence: 99%